The relationship between activities of daily living,falls and fear of falling in older adults : A crosssectional study (Bangladesh Journal of Medical Science, 2021)
Objective : Doingactivities of daily living can bring independence for the elderly. It can also maintain their health and social participation. However, experience of falls and fear of falling can affect the health and personal social life of the elderly. The aim of this study was to evaluate the relationship between falls and fear of falling with activities of daily living in older adults.Materials and methods : Four hundred and fifty elderly persons were enrolled in this cross-sectional study using cluster sampling. Demographic variables, Fall Efficacy Scale- International (FES-I) and questionnaires related to the study of activities of daily living were employed. To investigate advanced activities of daily living, open-ended questions were used. The history of falls within the last 12 months was investigated.Results : Mean score of basic activities of daily living in the elderly being studied was 15.49±1.74, and 95.4% of them were independent in doing these activities.Mean score of instrumental activities of daily living was 11.30±3.36, and 71.5% of them were independent in doing these activities. Participation of elderly persons in social activities was reported to be 77.9%. There was a significant relationship between activities of daily living (basic, instrumental, and advanced) and falls and fear of falling (p